SUCCESSFUL NEWS TEXT WRITING USING CYBER OBSERVATION TECHNIQUE IN GRADE VIII STUDENTS - siti sri jayati (SEAQIL Journal of Language Education, 2024)
This study aims to apply the cyber observation technique (ODM) to improve the writing skills of Grade VIII junior high school students. The research was conducted at Kasihan 1 Public Middle School, where 32 students were the research subjects during July-December 2022. Data collection techniques were observation and document analysis, and the data were analyzed through quantitative and qualitative analysis. The results of the study show that the ODM technique improves writing skills by cycle I. Students observe the virtual world of flag ceremony videos via LCD or WA, while in cycle II, ODM was applied to canteen service videos in schools. ODM techniques can improve news writing. Cycle I fulfilled the elements of 5 W, 1 H 100%, and the news structure reached three paragraphs (head, body, tail). The class average value was 87.81. KKM score of 75 reached 96.87%. In cycle II, elements of 5 W and 1 H were fulfilled 100%, and the news structure reached six paragraphs. Class average value of 90.28. KKM 75 achieved 100%. Students' positive response (easy/understand/happy) in writing news in cycle I reached 81.25%, while cycle II reached 100%.